Aloe-Emodin Isolated from Rheum Undulatum L. Regulates Cell Cycle Distribution and Cellular Senescence in Human Prostate Cancer LNCaP Cells - He, Mei Tong; Nguyen, Quynh Nhu; Cho, Eun Ju; Kim, Seung Hyun; Park, SeonJu; Park, Jun Yeon; Lee, Sullim; Kang, Ki Sung (Journal of dietary supplements, 2024)
Senescence can promote hyperplastic pathologies, such as cancer. Prostate cancer is the second most common type of cancer in men. The p21-mediate cellular senescence, facilitated through the tumor suppressor p53-dependent pathway, is considered the primary mechanism for cancer treatment. Aloe-emodin, has been reported to exert anticancer effects in various types of cancers. This study aimed to investigate the bioactivity of aloe-emodin in LNCaP cells the activation of p21-mediated cellular senescence. Aloe-emodin treatment increased the percentage of cells in the G1 phase while decreasing the percentage in the S phase. This effect was reflected in the expression levels of proteins associated with cell cycle progression, such as p21CIP, retinoblastoma protein, and cyclin-dependent kinase2/4 in LNCaP cells. However, aloe-emodin-treated LNCaP cells did not induce cell cycle arrest at G2/M checkpoint. Moreover, increased senescence-associated-galactosidase activity was observed in a dose-dependent manner following treatment with aloe-emodin. Aloe-emodin also induced DNA damage by modulating the expression of histone H2AX and lamin B1. Furthermore, aloe-emodin inhibited the proliferation of LNCaP cells, contrasting with the exponential growth observed in the nontreated cells. Importantly, this inhibition did not impact the immune system, as evidenced by the increased proliferation of splenocytes isolated from mice. These findings provide preliminary evidence of the anticancer effect of aloe-emodin in LNCaP cells, necessitating further investigations into the underlying mechanisms and human subjects.